2014
DOI: 10.1007/s10211-014-0206-4
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of antipredator training in captive-bred greater rheas reintroduced into the wild

Abstract: Your article is protected by copyright and all rights are held exclusively by Springer-Verlag Berlin Heidelberg and ISPA. This e-offprint is for personal use only and shall not be selfarchived in electronic repositories. If you wish to self-archive your article, please use the accepted manuscript version for posting on your own website. You may further deposit the accepted manuscript version in any repository, provided it is only made publicly available 12 months after official publication or later and provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 34 publications
1
13
1
Order By: Relevance
“…None of the eggs stayed in the nest for more than 24 hs to prevent the metabolism of the hormone by the developing embryo (Groothuis & von Engelhardt, 2005). Egg sample size was restricted to the maximum amount authorized in the Zoo, as the birds were also included in a reintroduction program (Lèche et al, 2016;Vera Cortez, Valdez, Navarro, & Martella, 2015). All eggs were collected during the intermediate laying period of each season, when the peak of egg production occurs (Lábaque, Martella, Maestri, Hoyos, & Navarro, 2010).…”
Section: Animals and Egg Collectionmentioning
confidence: 99%
“…None of the eggs stayed in the nest for more than 24 hs to prevent the metabolism of the hormone by the developing embryo (Groothuis & von Engelhardt, 2005). Egg sample size was restricted to the maximum amount authorized in the Zoo, as the birds were also included in a reintroduction program (Lèche et al, 2016;Vera Cortez, Valdez, Navarro, & Martella, 2015). All eggs were collected during the intermediate laying period of each season, when the peak of egg production occurs (Lábaque, Martella, Maestri, Hoyos, & Navarro, 2010).…”
Section: Animals and Egg Collectionmentioning
confidence: 99%
“…Approaching the study of the populations from both perspectives has allowed the development of scientific studies on the characteristics of the species, the individual and population variations, and their response to different environmental conditions . On the other hand, specific conservation actions have been addressed, reinforcing or repopulating areas where these species had suffered severe reductions or had disappeared, through the translocation of individuals produced in captivity (Bellis et al, 2004a;2004b;Vera Cortez et al, 2015). In addition, data were obtained on various aspects of the ecology of wild populations, which make it possible to evaluate and forecast the outcome of the possible actions (Bazzano et al, 2014;Giordano et al, 2010).…”
Section: Ecological Studiesmentioning
confidence: 99%
“…Each training session was filmed and lasted 18-19 min. Training with both models (Puma and chair) was performed in a similar way, but only the appearance of the Puma was paired to the presentation of the aversive stimulus (Vera Cortez et al 2015). Each individual received five sessions with each model.…”
Section: Animalsmentioning
confidence: 99%
“…In this case, the predator model was exhibited to the birds after training, but not associated with any aversive event. The animals actually learn to react against the predator and we observed that they modified the time they devoted to antipredator behaviours (for more details, see Vera Cortez et al 2015).…”
Section: Animalsmentioning
confidence: 99%
See 1 more Smart Citation